Pengaruh Debt Equity Ratio Terhadap Harga Saham Dimoderasi Oleh Earning Per Share - Bagaskara, Doni Yusuf; AC, Ali Mauludi (Akuisisi : Jurnal Akuntansi, 2023)
This study aims to determine the effect of Debt to Equity Ratio (DER) on stock prices with Earning Per Share (EPS) as a moderating variable. The population of this study is a manufacturing company in the food and beverage industry sub-sector which is listed on the Indonesia Stock Exchange. The sample used is a company with financial statements and annual reports containing information on DER, Stock Prices, and EPS from 2018 to 2020 totaling 51 samples. The analysis technique used is the outer model to test the value of each variable and the inner model to examine the relationship between variables. Data analysis using SmartPls software. The results showed that the Debt to Equity Ratio (DER) had no effect on stock prices. And also Earning Per Share (EPS) is not able to affect the relationship Debt to Equity Ratio (DER) to stock prices.